Effect of crop residue and fertilizers on humus fractions and rice (Oryza sativa) yield - PALKAR, K P; MESHRAM, N A; KASTURE, M C; PINJARI, S S; DODAKE, S B (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted during 2019–20 at the Research Farm of Dr. BSKKV, Dapoli, Maharashtra to study the effect of crop residues and fertilizers on humus fractions and rice yield in Alfisols. The study was conducted on ex situ incorporation of crop residue along with fertilizers and the results indicated that application of rice straw @2.5 t/ha + Ain leaf residue @2.5 t/ha along with 100% NPK was significantly beneficial for improving the content of soil humin, humic acid, fulvic acid and humic acid : fulvic acid (HA: FA) ratio and yield of rice. Crop residue and fertilizer management significantly improved the soil humin, humic acid, fulvic acid and humic acid: fulvic acid (HA: FA) ratio. Build-up of soil humus was due to the balanced application of crop residue along with fertilizers for developing bio-stability in soil which helps maintain soil health. In contrast, the application of 50%, 75% and 100% NPK alone did not gain optimum humus content in soil and yield of rice because of unbalanced use of fertilizers. Overall improvement in soil humus and yield of rice was observed by the integrated use of crop residue along with fertilizers in Alfisols.